DESIGNING "SUMMER" VISUAL NOVEL GAME AS AN ANGER MANAGEMENT GUIDE FOR INTROVERTED LATE ADOLESCENTS IN INDONESIA - Putri, Ni Wayan Yunita Wijaya; Haisnawa, Sri Maharani Budi; Utami, Lira Anindita (eProceedings of Art & Design, 2024)
Without proper understanding and the right way to manage it, anger could harm us andothers around us. Cases of murder and suicide with this emo}on as its mo}ve are the most severeexamples. Late adolescents who are s}ll faced with uncontrollable and unpredictable emo}ons intheir adolescence phase are vulnerable to their anger, especially those who are introverted as theyfeel emo}ons more intensely, and live in urban areas where human mobility and the pressure ofcommunity demands are high. Books about anger are published to help them understand their angerand how to manage it, but this learning media proved ine昀昀ec}ve. In this research, both qualita}veand quan}ta}ve methods will be used to gather data through interviews, observa}ons, literaturereviews, and a ques}onnaire. The gathered data will be analyzed with narra}ve inquiry, matrix, anddescrip}ve analysis methods. Through this project research, SUMMER is designed. It is a visual novelgame that ful昀椀lls Indonesian introverted late adolescents’ preferences and needs, which will helpthem be琀琀er understand their anger and how to manage it. Keywords: anger management, late adolescents, visual novel